The Cultural Lives of Domestic Objects in Late Antiquity - Stoner, Jo.
1 online resource.
Keywords: In this study, Jo Stoner investigates the role of domestic material culture in Late Antiquity. Using archaeological, visual and textual evidence from across the Roman Empire, the personal meanings of late antique possessions are revealed through reference to theoretical approaches including object biography. Heirlooms, souvenirs, and gift objects are discussed in terms of sentimental value, before the book culminates in a case study reassessing baskets as an artefact type. This volume succeeds in demonstrating personal scales of value for artefacts, moving away from the focus on economic and social status that dominate studies in this field. It thus represents a new interpretation of domestic material culture from Late Antiquity, revealing how objects transformed houses into homes during this period.